Graphene Nanoribbons on Highly Porous 3D Graphene for High‐Capacity and Ultrastable Al‐Ion Batteries. Issue 4 (11th November 2016) - Yu, Xinzhi; Wang, Bin; Gong, Decai; Xu, Zhi; Lu, Bingan
Abstract : Graphene nanoribbons on highly porous 3D graphene foam as the binder‐free cathode for flexible Al‐ion batteries exhibit low charge voltage, high capacity, excellent cycling ability (even after 10 000 cycles there is no capacity decay), and fast charging and slow discharging performance (the battery can be fully charged in 80 s and discharged in more than 3100 s).